The Spanish Civil War - Thomas, Hugh, 1931-2017 (A Touchstone Book, 1994)
What was it that roused left-wing sympathizers from all over the world to fight against Franco between 1936 and 1939? Why did the British and US governments refuse to intervene? And why did the Republican cause collapse so violently? Now revised and updated, Hugh Thomas's classic account presents the most objective and unbiased analysis of a passionate struggle where fascism and democracy, communism and Catholicism were at stake - and which was as much an international war as a Spanish one.